Endocrine mucin‐producing sweat gland carcinoma: Clinicopathologic, immunohistochemical, and molecular analysis of 11 cases with emphasis on MYB immunoexpression. (2nd July 2018) - Held, Laura; Ruetten, Arno; Kutzner, Heinz; Palmedo, Gabriele; John, Rahel; Mentzel, Thomas
Abstract : Background: Endocrine mucin‐producing sweat gland carcinoma (EMPSGC) is a rare low‐grade primary cutaneous sweat gland carcinoma with predilection for the periorbital skin in elderly female patients. Methods: We describe 11 cases of EMPSGC using a broad panel of immunohistochemical markers including BerEP4, cytokeratin 7, CAM 5.2, synaptophysin, chromogranin, cytokeratin 20, Ki67, progesterone receptor, and estrogen receptor. Calponin (1A4) and p63 were used to detect surrounding myoepithelial cells. We also examined staining with a relatively new marker, MYB. Previous studies of MYB on EMPSGC remain limited. As mucin‐rich basal cell carcinoma (BCC) represents a main differential diagnosis and primary cutaneous mucinous carcinoma (PCMC) could appear synchronous with EMPSGC, these lesions were also stained for MYB. Results: We found strong and homogenous nuclear MYB‐expression in 10 EMPSGC cases stained for MYB. MYB staining was not performed in one case. Furthermore, PCMC and mucin‐rich BCCs did not express MYB. Conclusion: The strong nuclear MYB‐positivity in EMPSGC could be useful as a new surrogate marker, especially in mucin‐poor EMPSGC cases. Additionally, the staining of PCMC revealed absent MYB‐expression leading to the conclusion that EMPSGC might not represent a precursor lesion for primary cutaneous mucinous carcinoma.